2014
DOI: 10.1037/a0037109
|View full text |Cite
|
Sign up to set email alerts
|

Morning employees are perceived as better employees: Employees’ start times influence supervisor performance ratings.

Abstract: In this research, we draw from the stereotyping literature to suggest that supervisor ratings of job performance are affected by employees' start times-the time of day they first arrive at work. Even when accounting for total work hours, objective job performance, and employees' self-ratings of conscientiousness, we find that a later start time leads supervisors to perceive employees as less conscientious. These perceptions in turn cause supervisors to rate employees as lower performers. In addition, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 57 publications
0
43
1
Order By: Relevance
“…In the HRM literature, a number of empirical studies have used supervisors' ratings to assess several employee outcomes, such as job performance (e.g. Yam, Fehr and Barnes, 2014), creativity (de Stobbeleir, Ashford and Buyens, 2011), customer service behaviours (Liden et al, 2014) and organizational citizenship behaviours (e.g. Bolino et al, 2006), among others.…”
Section: Data Collection and Results For Research Questionmentioning
confidence: 99%
“…In the HRM literature, a number of empirical studies have used supervisors' ratings to assess several employee outcomes, such as job performance (e.g. Yam, Fehr and Barnes, 2014), creativity (de Stobbeleir, Ashford and Buyens, 2011), customer service behaviours (Liden et al, 2014) and organizational citizenship behaviours (e.g. Bolino et al, 2006), among others.…”
Section: Data Collection and Results For Research Questionmentioning
confidence: 99%
“…The authors argued that these relationships arise because of a pervasive morning bias, that is, an association between beginning the day's activities early in the morning and goodness. Interestingly, supervisors who themselves are late chronotypes are less likely to hold negative stereotypes of employees with late start times, compared with supervisors who are early chronotypes (Yam et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be noted, however, that a shift of mindset is necessary in order to avoid disadvantages for employees who make use of flexible work times and decide to come to work later in the morning and finish work later in the evening. In a recent study, Yam, Fehr, and Barnes () showed that employees' start times influence supervisor performance ratings: Employees starting earlier were perceived as being more conscientious and better performers, even when accounting for total work hours and objective job performance. The authors argued that these relationships arise because of a pervasive morning bias, that is, an association between beginning the day's activities early in the morning and goodness.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires comprise a number of questions that participants are required to answer and are therefore usually a self‐report research method (Stone & Turkkan, ); although the same methods are sometimes used to rate others, such as supervisor ratings of performance (see, e.g., Yam, Fehr, & Barnes, ). Multi‐item psychometric scales, the focus of this article, are a specialized type of quantitative measure used in questionnaires (see, e.g., Nevill, Lane, Kilgour, Bowes, & Whyte, ) and the most frequently used measure in HRM research.…”
Section: Introductionmentioning
confidence: 99%